2011
DOI: 10.1007/s10209-011-0246-8
|View full text |Cite
|
Sign up to set email alerts
|

The Easyline+ project: evaluation of a user interface developed to enhance independent living of elderly and disabled people

Abstract: This paper reports the usability evaluation of interfaces developed to enable elderly and disabled people interact remotely with kitchen appliances in the home to enhance their independent living. A number of evaluation exercises were undertaken throughout the project's development, including user-participative workshops and focus groups. This paper focuses on the summative usability evaluation exercise, which comprised a laboratory-based study in a simulated home environment, with a view to determining the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Despite the high hopes invested in AAL technologies, research is still ongoing and rollout is at an early stage. Although many research projects are underway worldwide, including projects like Easyline+ (Picking et al, 2012) and Dem@Care (McHugh et al, 2012), very few clinical trials have yet been completed and rolled out to a large population.…”
Section: Ageing Of the World Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the high hopes invested in AAL technologies, research is still ongoing and rollout is at an early stage. Although many research projects are underway worldwide, including projects like Easyline+ (Picking et al, 2012) and Dem@Care (McHugh et al, 2012), very few clinical trials have yet been completed and rolled out to a large population.…”
Section: Ageing Of the World Populationmentioning
confidence: 99%
“…Thus, the form and consequences of dependency linked with the use of assistive technologies extend only to the dependency on a technical instrument (Remmers, 2010). Picking et al (2012) mention that researchers welcome the development of a certain amount of dependency on a product, if the product provides support for independent living. After all, according to Remmers (2010), such self-induced dependencies on artefacts are typical of modern civilisation.…”
Section: Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Related concepts Ambient intelligence ("ambient assisted living" OR "ambient intelligence" OR "smart home" OR "smart care" OR "smart service" OR "smart homecare" OR "ambient-intelligence environment" OR "smart environment" OR "home environment" OR "smart space" OR "home automation") AND Human-computer interaction ("usability" OR "accessibility" OR "human-computer interface" OR "user interface" OR "user interaction" OR "human-computer interaction" OR "user experience") AND Guidelines ("principles design" OR "guidelines" OR "heuristics" OR "rules") Picking et al 2012;Rugnone et al 2007; Shirehjini and Semsar 2017; Yilmaz 2019), 5 papers carried out end-users evaluations (Buzzi et al, 2019;Fogli et al, 2017;Goumopoulos & Mavrommati, 2020;Hafidh et al, 2017;Maguire, 2019), 4 papers used surveys (Buzzi et al, 2019;Hafidh et al, 2017;Huxohl et al, 2019;Licona and Droegehorn (2017)), 2 papers reported using interviews (Brich et al, 2017;Cha et al, 2019), and one paper mentioned a heuristic evaluation (Licona & Droegehorn 2017). All reported evaluations were carried out with users, having on average 34 users evaluating each studyranging from 3 users (Rugnone et al (2007)) to 136 users (Brauner et al, 2017) to 136 users (Brauner et al, 2017) involved in each evaluation.…”
Section: Introductionmentioning
confidence: 99%